2009
DOI: 10.1002/dvg.20530
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of Pcipg2 from the straminopilous plant pathogen Phytophthora capsici

Abstract: Phytophthora capsici causes serious diseases in numerous crop plants. Polygalacturonases (PGs) are cell wall-degrading enzymes that play an important role in pathogenesis in straminopilous pathogens. To understand PGs as they relate to the virulence of P. capsici, Pcipg2 was identified from a genomic library of a highly virulent P. capsici strain. Pcipg2 was strongly expressed during symptom development after the inoculation of pepper leaves with P. capsici. The wild protein (PCIPGII) was obtained from the exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 43 publications
1
35
0
Order By: Relevance
“…Highly virulent Phytophthora capsici strain SD33 has been tested in our laboratory and routinely cultured on 10% V8-juice agar medium at 25°C [51,66,67]. Production of sporangia and zoospores were performed as previously described [67].…”
Section: Methodsmentioning
confidence: 99%
“…Highly virulent Phytophthora capsici strain SD33 has been tested in our laboratory and routinely cultured on 10% V8-juice agar medium at 25°C [51,66,67]. Production of sporangia and zoospores were performed as previously described [67].…”
Section: Methodsmentioning
confidence: 99%
“…The role of pectate lyase in the pathogenicity of Colletotrichum gloeosporioides has been proven through expression of its coding gene in the weakly pathogenic species Colletotrichum magna, which led to the enhancement of its pathogenicity [37]. More recently, the activity of pectate lyase was strongly correlated to the pathogenicity levels of Phytophthora capsici isolates [38].…”
Section: Discussionmentioning
confidence: 98%
“…Highvirulent P. capsici strain SD33 [5,10] was used in these studies, and genomic DNA was extracted as previously described [21]. A genomic library of P. capsici was constructed as previously described [11] and screened using five pairs of degenerate primers (Table 1) designed ba- Table 1. The primers used for gene cloning in this study.…”
Section: P Capsici Strain Isolation Of Pcpme Genes and Sequence Anamentioning
confidence: 99%
“…Pectin methylesterase (PME; EC 3.1.1.11) removes the methyl group from esterified galacturonic acid residues in pectin chains [9]. Our previous studies revealed that the CWDEs were contributing to virulence of P. capsici during the course of infection [10,11] in a manner similar to that of CWDEs from bacterial [12,13] and fungal pathogens [14 − 17]. These studies have shown that pectinases, which are among the CWDEs secreted by P. capsici, play an important role in the infection process.…”
mentioning
confidence: 99%
See 1 more Smart Citation